A processable Prussian blue analogue-mediated route to promote alkaline electrocatalytic water splitting over bifunctional copper phosphide. Issue 35 (22nd August 2022) - Chen, Jiahui; Li, Yunming; Ye, Huangqing; Zhu, Pengli; Fu, Xian-Zhu; Sun, Rong
Abstract : 3D copper foam supported core–shell Cu3 P@Co-Cu3 P, which is prepared by a Prussian blue analogue-mediated route, has been demonstrated as an efficient electrocatalyst for alkaline overall water splitting. Abstract : Prussian blue analogues (PBAs) as a class of metal–organic frameworks demonstrate a promising platform to develop cost-effective high-performance electrocatalysts. However, the construction of delicate micro/nanostructures and controllable doping are still a challenging task for the fabrication of highly efficient copper-based electrocatalysts. Herein, we report a facile synthesis of copper foam supported Cu3 P@Co-Cu3 P (CH@PBA-P/CF) sub-microwire arrays as an active electrocatalyst for alkaline water splitting. The Co-Cu3 P shell derived from the Cu3 [Co(CN)6 ]2 PBA serves as the source of active sites. Co doping and construction of core–shell structures endow the CH@PBA-P/CF electrocatalyst with abundant catalytic sites, enhanced intrinsic activity, and low charge transport resistance. The catalytic electrode integrated with 3D copper foam and 1D sub-microwire arrays is highly conductive and stable, which promotes the charge transport and improves the structural stability. As a consequence, CH@PBA-P/CF shows impressive catalytic performances toward the HER and OER in terms of low overpotentials of 231 and 312 mV at a current density of 50 mA cm −2 in 1 M KOH, respectively. Notably, the water electrolyzer using the CH@PBA-P/CF electrode exhibits better water splitting performance than the one using noble metal-based couples.